1995
DOI: 10.1073/pnas.92.6.2046
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the human guanylin gene and the processing and cellular localization of the peptide.

Abstract: The complete cell biological analysis of human guanylin, a recently discovered regulatory peptide, is offered in this investigation: (i) the nucleotide sequence of the gene, (ii) the isolation and characterization of its circulating molecular form, and (iii) its localization in enterochromaffin cells of the gut. As determined by molecular cloning, DNA sequencing, and comparison with the known cDNA sequence, the approximately 2.6-kbp large gene consists of three exons interrupted by two introns. The putative pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 39 publications
(58 reference statements)
1
27
0
Order By: Relevance
“…This is in clear contrast to our results, where maximum receptor expression is detected in the colonic crypts. In the human intestine, a single report suggested that guanylin was expressed in the epithelium of the crypts of Leiberkühn in the secretory mucosa [Hill et al, 1995] and we do detect receptor expression in these cells in the rat.…”
Section: Discussionmentioning
confidence: 88%
“…This is in clear contrast to our results, where maximum receptor expression is detected in the colonic crypts. In the human intestine, a single report suggested that guanylin was expressed in the epithelium of the crypts of Leiberkühn in the secretory mucosa [Hill et al, 1995] and we do detect receptor expression in these cells in the rat.…”
Section: Discussionmentioning
confidence: 88%
“…A human genomic library in phage (Stratagene) was screened as described (2) by using a partial 269-bp, HCC-1-specific cDNA fragment (1) as a probe. Three independent clones were isolated, and the SstI restriction fragments of one of them were subcloned into pBSK ϩ .…”
Section: Methodsmentioning
confidence: 99%
“…Northern blot and immunohistochemical analysis have revealed that guanylin occurs in the mucosa of the mammalian intestine (see reviews [4] and [5]). The peptide is probably released from entero-endocrine cells [6,7] into the intestinal lumen to activate the GC-C and consequently the chloride transport in enterocytes by means of a paracrine interaction [5]. However, several data indicate that the guanylin/GC-C system is not exclusively confined to the intestine.…”
Section: Introductionmentioning
confidence: 99%